Technical platform on the measurement and reduction of food loss and waste - International Food Policy Research Institute; Food and Agricultural Organization of the United Nations (International Food Policy Research Institute, 2015)
Each year, an estimated one-third of all food produced for human consumption is lost or wasted world-wide. The social, economic, and environmental impacts of food losses and waste (FLW) must be addressed concurrently due to their direct and significant impact on food and nutrition security, natural resources, and climate change. The Platform facilitates local, national and regional level food loss and waste prevention, reduction and measurement.